‘Why Bibliotherapy?’ A Content Analysis of its Uses, Impediments and Potential Applications for School Libraries - Garrett Davis, Christine A. (Qualitative and Quantitative Methods in Libraries, 2019)
This paper is a historical examination of the use of bibliotherapy, its impediments and potential resolutions. It has been more than ninety years since Sadie Peterson Delaney, chief librarian of the United States Veterans Administration Hospital in Tuskegee, Alabama worked with a team of social workers and psychiatrists to practice bibliotherapy on World War I Veterans. Bibliotherapy is supported by the age-old ideological concept of the ‘healing power of books’ (Lehr, 1981). For decades, theoretical arguments have ensued regarding its questionable success as a treatment, the efficacy of its use and the competency of its practitioners. The primary antagonists seem to be proponents of evidence-based medicine (EBM) with meta-analysis as its statistical methodology for assessing clinical effectiveness. In recent years, bibliotherapy has acquired some stature as a recognized therapeutic activity (Jack & Ronan, 2008). Bibliotherapy schema are appearing in schools at increasing rates as an adjunct program for students experiencing loss, victims and perpetrators of bullying, and special needs students with physical and learning disabilities. Many students enter the educational system lacking the necessary social, emotional, and academic prerequisites to be successful. Bibliotherapy is perceived as one strategy to overcome such societal impediments (Cook, Earles-Vollrath, & Banz, 2006; Iaquinta & Hipsky, 2006). In addition to its academic function, the school library is a place where children and teenagers absorb cultural values and where bibliotherapy can play a humanistic role in their social and emotional development (Jurkowski, 2006). This paper examines several proactive perspectives such as training in bibliotherapeutic practices in library science degree programs for school librarians. Rubin (1978) suggested that librarians view their role in bibliotherapy as a possible path toward students’ self-actualization (Baruchson-Arbib, 2000).